Clinical, laboratory, and procedural predictors of slow flow/no reflow phenomenon after emergency percutaneous coronary interventions in ST-elevated myocardial infarction - Fatemeh Bamarinejad; Mohammad Kermani-alghoraishi; Azam Soleimani; Hamidreza Roohafza; Safoura Yazdekhasti; Maedeh Azarm; Atefeh Bamarinejad; Masoumeh Sadeghi (The Egyptian Heart Journal)
Abstract Background Emergency percutaneous coronary intervention (PCI) is a common treatment for ST-elevated myocardial infarction (STEMI) patients. However, the coronary slow flow/no reflow phenomenon (CSF/NRP) can occur as a complication during or after the procedure. Identifying predictors of CSF/NRP after emergency PCI in STEMI patients can help clinicians anticipate and prevent this complication. In this study, we aimed to investigate clinical, laboratory, and procedural factors that may contribute to the development of CSF/NRP in STEMI patients undergoing PCI. Results A total of 460 patients were included in this study, with a mean (± SD) age of 60 ± 12.5 years. The incidence of CSF/NRP was 30.2% (n = 139) among the study population. The univariate analysis showed that older age, lower left ventricular ejection fraction (LVEF), initial thrombolysis in myocardial infarction (TIMI)flow grade 0–2, increased creatinine level, lower estimated glomerular filtration rate (eGFR), diffuse target lesion length, and longer length of stent were significantly associated with the occurrence of CSF/NRP (p < 0.05). However, in the multivariate logistic regression model, only eGFR (OR = 0.98, 95% CI: 0.96–0.99, p = 0.005), diffuse target lesion length (OR = 2.15, 95% CI: 1.20–3.83, p = 0.009) and LVEF (OR = 0.96, 95% CI: 0.94–0.98, p = 0.004) remained significant predictors of CSF/NRP. Conclusions The present study demonstrated that diffuse lesion length, lower LVEF, and lower eGFR can be considered as independent predictors of CSF/NRP in STEMI patients.